2023
DOI: 10.1002/eap.2816
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐informed forecasts reveal dramatic local habitat shifts and population uncertainty for northern boreal caribou

Abstract: Most research on boreal populations of woodland caribou (Rangifer tarandus caribou) has been conducted in areas of high anthropogenic disturbance. However, a large portion of the species' range overlaps relatively pristine areas primarily affected by natural disturbances, such as wildfire. Climate-driven habitat change is a key concern for the conservation of boreal-dependent species, where management decisions have yet to consider knowledge from multiple ecological domains integrated into a cohesive and spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
(102 reference statements)
0
0
0
Order By: Relevance
“…Erlandsson et al reported that the design of the datasets was likely unable to compensate for spatial autocorrelation and that the results are suspected to be overly optimistic [29]. The low number of training samples (3,290) and complex structure of this model may also indicate an overdetermined CNN, further supporting the authors' conclusion.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Erlandsson et al reported that the design of the datasets was likely unable to compensate for spatial autocorrelation and that the results are suspected to be overly optimistic [29]. The low number of training samples (3,290) and complex structure of this model may also indicate an overdetermined CNN, further supporting the authors' conclusion.…”
Section: Introductionmentioning
confidence: 65%
“…In 2016, Rangifer tarandus, commonly known as the caribou, was categorized as a vulnerable species due to an observed decline of 40% between the 1990s and 2015 [1]. Caribou populations are threatened by changes to their habitat, unregulated hunting, and herd fragmentation due to human-made infrastructure [1][2][3]. Terricolous (ground-dwelling) lichen is a primary food source for caribou, comprising 75% and 25% of their winter and summer diets respectively [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation